The Influence of Advertising, Ratings, and E-Wom on Consumer Purchase Intention In Shopee Live Products - Deshinta Ardya Putri; Ali (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aim to examine the influence of advertising, ratings, and E-WOM on consumer purchase intention on Shopee Live in the Jepara area. This research is a quantitative study utilizing a survey method. The population of this study consists of Shopee Live viewers in Jepara, with the sample being those who have made a purchase. The sample was selected using purposive sampling, consisting of 96 individuals who had previously purchased products on Shopee Live. Data was collected through an online questionnaire that had undergone validity and reliability tests. The type of data used in this research is primary data, which was distributed to respondents and then analyzed using Partial Least Squares (PLS) and processed with SmartPLS 4.0. The research findings reveal that advertising and E-WOM significantly influence purchase intention. However, ratings do not have a significant effect on purchase intention. These findings are expected to provide crucial insights for sellers in developing more effective sales strategies to enhance consumer purchase intention on the Shopee platform.